Discriminación, imagen y sexismo en la prensa mexicana - Treviño, María Eugenia Flores (Comparative Cultural Studies: European and Latin American Perspectives, 2019)
The sexism and verbal violence are present in the speeches of Mexican politicians and they constitute discrimination. This work continues the qualitative and descriptive approximation to the verbal acts (Im) polite expressed against women in the press of Mexico. Ten articles are reviewed with phrases from political actors documented in the press, to describe the pragmatic-rhetorical and semiotic-discursive strategies used in these acts of sexism. The sample is by random, the selection of the fragments is designed by the topic and lacks representative criteria. The theoretical supports are constituted by the positions of Kaul de Marlangeon (2005, 2006); Goffman (1963), Pêcheux (1970), Foucault (1970), Haidar (2006), Bravo & Briz (2005), Austin (1962). Trends offer data on degradation, female image injuries, objectification of the subject referred and discourtesy by fustigation. It is also exercise the functions of political discourse (Chilton & Schäffner 2008): Coercion, legitimation and delegitimization.